Assessing temperature signal in X-RAY densitometric data of norway spruce and the earliest instrumental record from the Carpathi - Kern, Zoltán; Popa, Ionel (Journal of Environmental Geography, 2009)
Radiodensity data derived from Norway spruce were studied from a southern Carpathian site. Maximum density record showed significant positive relationship (r=0.59) with the growing season (April-September) air temperature and minimum density (MND) record showed clear and significant negative response (r=-0.41) to June-July mean air temperature. This significant MND response to climate is a novel result as traditionally this densitometric parameter was regarded not to carry any meaningful climatic signal. Derived temperature sensitive proxy records were compared to instrumental data of Sibiu (Nagyszeben/Hermannstadt) the oldest available regional station. Results of the running window correlation analysis pointed out notable inhomogeneities in the instrumental data before 1906. The Sibiu temperature series should be subjected to scrutiny revision to clean it from inhomogeneities.